Incorporating Cultural Background in Teaching EFL Writing in Libyan: A Critical Literature Review - Fathia Baresh, Eman (LP2M IAIN Sultan Amai Gorontalo, 2024)
This study explores the crucial influence of cultural background on the writing performance of English as a Second Language (ESL) and English as a Foreign Language (EFL) students, focusing specifically on the Libyan context. The impact of cultural background is observed across various dimensions of writing, encompassing content, organization, style, language, and conventions. Additionally, cultural backgrounds shape the writing strategies adopted by EFL and ESL learners. Considering the significance of this influence, the paper advocates for awareness among EFL and ESL teachers regarding the cultural backgrounds of learners when designing or adopting instructional techniques for teaching EFL writing. The literature review critically examined the roles played by learners' cultural backgrounds in shaping their writing skills. It explores the role of the English language in Libya and assesses the current practices in teaching EFL writing within the Libyan educational landscape. The study discovered that very few studies have been conducted concerning EFL and cultural background in the Libyan context. Thus, it identifies challenges faced by Libyan undergraduates in EFL writing due to their different cultural and linguistic backgrounds, which differ from that of the English language. In conclusion, this study offers valuable insights into the complex relationship between cultural background and EFL writing performance. The paper contributes to a deeper understanding of the challenges faced by Libyan students and provides practical recommendations for instructors. Furthermore, the study identifies potential avenues for future research in the dynamic field of EFL writing instruction.